Determinants of Repurchase Intention Mediated by Customer Satisfaction Among “X” Coffee Application Users - Tjandra, Sabrina Layman; Rodhiah (Yayasan Gema Bina Nusantara, 2025)
This research aims to analyze and ascertain how repurchase intention among users of the